Atypical relaxation of structural constraints in Hox gene clusters of the green anole lizard - Di-Poï, Nicolas; Montoya-Burgos, Juan I.; Duboule, Denis (Genome Research, 2009)
Hox genes control many aspects of embryonic development in metazoans. Previous analyses of this gene family revealed a surprising diversity in terms of gene number and organization between various animal species. In vertebrates, Hox genes are grouped into tightly organized clusters, claimed to be devoid of repetitive sequences. Here, we report the genomic organization of the four Hox loci present in the green anole lizard and show that they have massively accumulated retrotransposons, leading to gene clusters larger in size when compared to other vertebrates. In addition, similar repeats are present in many other development-related gene-containing regions, also thought to be refractory to such repetitive elements. Transposable elements are major sources of genetic variations, including alterations of gene expression, and hence this situation, so far unique among vertebrates, may have been associated with the evolution of the spectacular realm of morphological variations in the body plans of Squamata. Finally, sequence alignments highlight some divergent evolution in highly conserved DNA regions between vertebrate Hox clusters, which may coincide with the emergence of mammalian-specific features.